Stone mastic asphalt (SMA) with crumb rubber according to a new dry-hybrid technology: A laboratory and trial field evaluation. (10th September 2018) - Sangiorgi, Cesare; Tataranni, Piergiorgio; Simone, Andrea; Vignali, Valeria; Lantieri, Claudio; Dondi, Giulio
Highlights: A new dry-hybrid technology is proposed for the addition of crumb rubber into SMAs. SMA1.20 has mechanical properties comparable to SMAnR and higher than SMA0.75. Good Skid resistance and MTD values are recorded for rubberized sections. Both the rubberized surfaces reduce the emission of noise if compared to SMAnR. Environmental benefits deriving from the new dry-hybrid technology are confirmed. Abstract: Today the use of recycled and second-hand materials can be considered as a suitable solution for the construction or the rehabilitation of road pavements. The increasing interest in this process lead to the study and the evaluation of different waste materials, not directly connected to the construction field, among these Crumb Rubber from end-of-life tires. To date, this recycled material has been added into bituminous mixes for road pavements according to several technologies, for the production of different mixtures. In the present paper, the crumb rubber was used for the production of Stone Mastic Asphalt (SMA) according to a new dry-hybrid technology. A full laboratory investigation and a trial field study are here presented. A complete physical and mechanical characterization was carried out to define a specific mix design. Once defined these properties, a full-scale test section was constructed: specific in situ tests and collection of samples were planned. In both the laboratory and trial field phases, tests results were always compared to those obtained with a traditional SMA mixture. In an environmental prospective, fumes and emissions during laying were also analyzed. The goal of this research project was to analyze and evaluate the different physical, mechanical and functional characteristics induced by the use of Crumb Rubber for the production of SMA mixtures according to the proposed new dry-hybrid technology. As overall result, the presence of Crumb Rubber does not seem to negatively affect the volumetric properties of the mixture. SMA1.20 shows mechanical properties comparable to the reference mixture and higher if compared to SMA0.75. As for the acoustic properties, both the rubberized surfaces reduce the emission of noise if compared to the traditional SMA layer. The monitoring of pollutants during paving operations confirms the effective environmental benefits deriving from the use of the new dry-hybrid technology here proposed.